Alumina supported nano-platinum on copper nanoparticles prepared via galvanic displacement reaction for preferential carbon monoxide oxidation in presence of hydrogen. (5th November 2019) - Khobragade, Rohini; Yearwar, Divya; Labhsetwar, Nitin; Saravanan, Govindachetty
Abstract: Improved catalytic centres with a minimum mass-loading of expensive platinum (Pt) have been anticipated for various catalytic applications, for instance preferential oxidation (PROX) of carbon monoxide (CO) in the presence of Hydrogen. Here, we report the synthesis of nano-Pt on the surface of copper (Cu) nanoparticles (NPs) supported on γ-Al2 O3 (Pt n (Cu)/γ-Al2 O3 ) via galvanic displacement reaction (GDR) for the catalytic CO-PROX reaction. Pt n (Cu)/γ-Al2 O3 showed much improved CO-PROX performance compared to that of the as-synthesized Pt l (Cu)/γ-Al2 O3 catalyst. Importantly, no significant conversion of hydrogen at a lower temperature range (<200 °C) is observed during the CO-PROX reaction which is one of the essential prerequisites for the CO-PROX reaction. Moreover, Pt n (Cu)/γ-Al2 O3 showed the durable, long-term catalytic CO-PROX performance for 120 h. These results infer that realization of nano-Pt on the surface of the Cu NPs holds the promise as the catalytic centres with the minimum mass-loading of Pt for the CO-PROX reaction. Graphical abstract: Image 1 Highlights: Nano-Pt on the surface of copper (Cu), [Pt n (Cu)] was prepared via galvanic displacement reaction. Pt n (Cu) showed improved preferential carbon monoxide oxidation (CO-PROX) performance. Pt n (Cu) showed no significant hydrogen conversion under CO-PROX conditions. Pt n (Cu) showed the durable, long-term catalytic CO-PROX performance.